Ultrasound-guided percutaneous peripheral nerve stimulation for analgesia following total knee arthroplasty: a prospective feasibility study. Issue 1 (December 2017) - Ilfeld, Brian; Gilmore, Christopher; Grant, Stuart; Bolognesi, Michael; Del Gaizo, Daniel; Wongsarnpigoon, Amorn; Boggs, Joseph
Abstract Background Peripheral nerve stimulation has been used for decades to treat chronic pain but has not been used for postoperative analgesia due to multiple limitations, beginning with invasive electrode placement. With the development of small-diameter/gauge leads enabling percutaneous insertion, ultrasound guidance for accurate introduction, and stimulators small enough to be adhered to the skin, neurostimulation may now be provided in a similar manner to continuous peripheral nerve blocks. Here, we report on the use of ultrasound-guided percutaneous peripheral nerve stimulation to treat postoperative pain. Materials and methods Subjects within 60 days of a total knee arthroplasty with pain insufficiently treated with oral analgesics had a 0.2-mm-diameter electrical lead (pre-loaded into a 20 gauge needle) introduced percutaneously using ultrasound guidance with the tip located approximately 0.5–1.0 cm from the femoral nerve (a second lead was inserted approximately 1.0–3.0 cm from the sciatic nerve for posterior knee pain). An external stimulator delivered current. Endpoints were assessed before and after lead insertion and the leads subsequently removed. Due to the small sample size for this pilot/feasibility study, no statistics were applied to the data. Results Leads were inserted in subjects (n = 5) 8–58 days postoperatively. Percutaneous peripheral nerve stimulation decreased pain an average of 93% at rest (from a mean of 5.0 to 0.2 on a 0–10 numeric rating scale), with 4 of 5 subjects experiencing complete resolution of pain. During passive and active knee motion pain decreased an average of 27 and 30%, respectively. Neither maximum passive nor active knee range-of-motion was consistently affected. Conclusions Ultrasound-guided percutaneous peripheral nerve stimulation may be a practical modality for the treatment of postoperative pain following orthopedic surgical procedures, and further investigation appears warranted.